How sweet it is: Honey is in! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Perspectives for honey production in the tropics. Edited by M J Sommeijer, J Beetsma, W-J Boot, E-J Robberts and R de Vries. 1997. 214 pp. ISBN 90 801204 3 X NECTAR PO Box 141 6720 AC Bennekom The Netherlands. Fax: +31 842 103374 Email: nectar@wxs